Fraglilitas Eritrosit Anjing Lokal Bali (THE FRAGILITY OF ERYTHROCYTE ON LOCAL DOGS IN BALI) - Siswanto, Siswanto; Putra, I Gusti Agung Arta; Utami, Ida Ayu Putri; Soma, I Gede (Jurnal Veteriner; Vol 2 No 3 (2001), 2016)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text
Keywords: fragility; erytrhocyte; dog